2010
DOI: 10.1590/s1982-56762010000600002
|View full text |Cite
|
Sign up to set email alerts
|

Use of osmotic solutions for inhibition of sunflower seed germination in blotter test

Abstract: The aim of this work was to investigate the feasibility of using a water restriction technique with osmotic solutes to control sunflower (Helianthus annuus L.) seed germination in blotter tests. The effects of water potential (-0.8 MPa -Megapascal, -1.0 MPa, -1.2 MPa and -1.4 MPa) of substrates osmotically modified with sodium chloride or mannitol were evaluated for seed germination, radicle length and mycoflora present in the samples. The effects of levels of osmotic potentials ranging from -0.35 MPa to -1.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Germination rate of each lupin cultivar used in this study decreased as osmotic potential increased. Similar results were observed in cotton, rice, sunflower, and common bean seeds [53,56,57]. Several studies reported that the incubation period to obtain inoculated seeds ranged between 24 and 144 h [58,59,60,61].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Germination rate of each lupin cultivar used in this study decreased as osmotic potential increased. Similar results were observed in cotton, rice, sunflower, and common bean seeds [53,56,57]. Several studies reported that the incubation period to obtain inoculated seeds ranged between 24 and 144 h [58,59,60,61].…”
Section: Discussionsupporting
confidence: 76%
“…Osmotic potential of −0.8 (33.10 g L −1 ), −1.0 (47.75 g L −1 ), and −1.2 (62.46 g L −1 ) MPa was used for the incorporation of the osmotic solute into the PDA medium. The osmotic potential of PDA without the solute was estimated to be −0.35 MPa [57]. Agar plugs (6 mm diameter) were removed from the edge of an actively growing colony of C. lupini (isolate IMI504893) and placed at the center of PDA plates (9 cm) amended with mannitol.…”
Section: Methodsmentioning
confidence: 99%